2021
DOI: 10.1007/s11517-021-02379-x
|View full text |Cite
|
Sign up to set email alerts
|

A new conditional region growing approach for microcalcification delineation in mammograms

Abstract: Microcalcifications (MCs) are considered as the first indicator of breast cancer development. Their morphology, in terms of shape and size, is considered as the most important criterion that determines their malignity degrees. Therefore, the accurate delineation of MC is a cornerstone step in their automatic diagnosis process. In this paper, we propose a new conditional region growing (CRG) approach with the ability of finding the accurate MC boundaries starting from selected seed points. The starting seed po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Proposed a new segmentation method [ 26 ] based on the conditional region growing [ 12 , 13 ] approach for mammographic images, but the method is dependent on the order of the pixels processed thus results may vary for medical images. Introduce improved region growing (IRG) method [ 27 ] to segment lung tumor with less time and more accuracy. In the [ 28 ] proposed a method of segmenting medical images based on neural networks (NN) and fuzzy connectedness.…”
Section: Background and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Proposed a new segmentation method [ 26 ] based on the conditional region growing [ 12 , 13 ] approach for mammographic images, but the method is dependent on the order of the pixels processed thus results may vary for medical images. Introduce improved region growing (IRG) method [ 27 ] to segment lung tumor with less time and more accuracy. In the [ 28 ] proposed a method of segmenting medical images based on neural networks (NN) and fuzzy connectedness.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Text Segmentation [1] Region Growing [12,13] Fuzzy connectedness [28] Graph Cut [27,28] Random Walk [28,29] Watershade [30,31] Hard Clustering [35][36][37][38] Soft Clustering [39][40][41][42] C-Means [45][46][47][48][49] K-Means [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] Fusion Based…”
Section: Machine Learningmentioning
confidence: 99%
“…According to Touil et al [13] suggested a new conditional region growth (CRG) method for determining correct MC bounds beginning from a set of seed points. Regional maxima detection and superpixel analysis are used to find the beginning seed points.…”
Section: Literature Reviewmentioning
confidence: 99%